Pengembungan Hidrogel Selulosa Bakteria-asid Akrilik : Sensitiviti Terhadap Rangsangan Luar - Nadia Halib; Mohd Cairul Iqbal Mohd Amin; Ishak Ahmad; Zulkifli Mohamed Hashim; Noriah Jamal (Penerbit UKM, 2024)
This study evaluated various environmental factors affecting the swelling degree of bacterial cellulose-acrylic acid hydrogels. Aqueous bacterial cellulose-acrylic acid (4:1) mixtures were prepared and subjected to electron beam irradiation at 30 and 50 kGy. Swelling rate under influenced of pH, temperature and ionic strength was investigated from 1 to 24 hours. Swelling degree of hydrogels was dependent on irradiation dose: those synthesized at 50 kGy exhibited significant higher swelling degree (p<0.0001) in methanol (619%) compared to water (510%) at room temperature after 24 hours. External ionic strength affected swelling, i.e, elevation in sodium chloride concentration decreased swelling degree. Hydrogels were also sensitive to pH: swelling increased with increasing pH and was optimal at pH 7. Swelling also increased with increasing temperature from 25¡C to 50¡C. In conclusion, the ability of electron irradiated bacterial cellulose-acrylic acid hydrogels to respond to various external environment make it a material to be developed as an active delivery system for drugs, proteins and hormones.